Teachers’ Attitudes and Classroom Engagement: Perceptions from Forestry Students in Politeknik Pertanian Negeri Kupang - Pratiwi, Gadis Kartika; Oktaviani, Eva (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
Lecturers in vocational education institutions exhibit unique characteristics in delivering instruction and supporting student learning, particularly in practical classes that emphasize real-world experiences and industry-related skills. This study explores students’ perceptions of lecturers' attitudes and their influence on student engagement in the Forestry Department of the State Agricultural Polytechnic of Kupang. Using a qualitative case study approach, data were collected through semi-structured interviews with eight students and analyzed using inductive thematic analysis. The findings reveal that key aspects of lecturers' attitudes influencing student engagement include enthusiasm in teaching, fairness in treatment, and supportive responses to students’ questions and mistakes. While no distinctive attitudes specific to vocational lecturers were identified, the study found that students in East Nusa Tenggara possess unique cultural and linguistic traits, which shape their perceptions of lecturers' attitudes. These findings underscore the importance of enhancing the pedagogical competencies of vocational lecturers to create a participatory, equitable, and contextually relevant learning environment, particularly in regions with diverse cultural and linguistic backgrounds.